Dialog czy misja? Dokumenty misyjne Kościoła wobec dialogu międzyreligijnego - Magdalena Rzym, (Annales Missiologici Posnanienses, 2019)
The Second Vatican Council opened a new perspective for interreligious dialogue for the Church. Theological reﬂection, including non-Christian religions, pointed out the elements of truth and holiness present in them and conﬁrmed their value as preparation for the Gospel. This positive image of religion does not conﬂict with missionary activity. The conciliar and post-conciliar documents of the Church emphasize the constant validity of the missionary mission of Christians and indicate dialogue as one of the forms of mission. Signiﬁcantly, the topic of interreligious dialogue is primarily addressed in missionary documents that recognize it as an integral part of the preaching of the Gospel. The Council decree Ad gentes divinitus, the exhortation of Paul VI Evangelii nuntiandi, the encyclical of John Paul II Redemptoris missio are just some of the Church’s many missionary documents that develop the concept of interreligious dialogue.